Lymphocytic esophagitis: a histologic pattern with emerging clinical ramifications. Issue 1 (16th September 2016) - Lisovsky, Mikhail; Westerhoff, Maria; Zhang, Xuchen
Abstract : The clinical significance of lymphocytic esophagitis (LyE), which is characterized by the prominence of peripapillary intraepithelial lymphocytes (IELs) without significant granulocytosis, remains poorly understood. During the last few years, plausible clinical correlates and novel approaches for stratification of LyE have started to emerge. Association with Crohn's disease has been established in children, but is not observed in adults. In adults, the form of LyE showing CD4 + ‐predominant IELs has been recently found to be associated with non‐achalasia primary motility abnormalities. GERD is another possible association. The most common clinical manifestations of adult LyE are dysphagia and normal endoscopic appearance of the esophagus. LyE should be reported by pathologists in order to distinguish it from its mimics, such as eosinophilic esophagitis, and to assist in directing the next steps in evaluation for known associated diseases, such as Crohn's disease or motility disorders.